Novel Organic-Inorganic Hybrid Polystyrene Nanoparticles with Trichromatic Luminescence for the Detection of Latent Fingerprints - Xiao Wang; Tao Liao; Haiyan Wang; Hongxia Hao; Qinglai Yang; Hong Zhou; Yu Ma; Minjie Zhi; Jiahao Wang; Ruihang Fan (International Journal of Analytical Chemistry)
This article explored the application of novel organic-inorganic hybrid polystyrene nanoparticles (PSNPs) with trichromatic luminescence for the detection of latent fingerprints. The PSNPs were synthesized by encapsulated Eu(DBM)3phen, coumarin 6, and FDBT into the polystyrene nanoparticles through the swelling method and applied them to visualize latent fingerprints. The PSNPs had a spherical morphology with an average diameter of 310.7 nm, and they emitted trichromatic fluorescence (525 nm/570 nm/610 nm) under 365 nm excitation wavelength with green/yellow/red color under filters. They were less likely to aggregate, float or stain the background when treating fingerprints. The developed fingerprints with excellent clarity of ridges and contrast could be viewed, and the digital magnification of fluorescence-developed fingerprints provided more minutiae details about some regional patterns. The colorimetric and fluorescent trichromatic light could provide complementary signals without the background interference from fluorescent substrates and/or complex multicolor surfaces, which improved the applicability of fluorescent nanoparticles for fingerprints development. PSNPs are promising for the detection of latent fingerprints and practical criminal investigations with their ease of operation, eco-friendly properties, and excellent trichromatic optical performance.